(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Retail Marketing defined as“individuals or groups, acquiring, using and disposing of products, services,ideas or experiences” (Arnould, Price & Zinkha, 2004). There are numbers ofdifferent theories explaining Retail Marketing (Statt, 1997; Blackwell,Minrard, and Engel, 2006; Chaudhuri, 2006) and a huge amount of literaturecurrently exists (Grunert 2002; Botonaki, Ploymeros, Tsakorodou, & Mattas,2006; Friese, Wanke, and Plessner, 2006). There are different number ofcharacteristics, which can impact on Retail Marketing (Figure 1), whichincludes from demographic variables to purchase and consumption behaviours.